Pretty in Prozac: The role of social connectedness in the declining life satisfaction of Australian females - Ulichny, J; Ulichny, Jennifer (My University, 2014)
Despite an increased effort to better understand well-being, studies in the USA and Britain suggest that there has been an overall decline in reported well-being since the 1970’s, particularly for females. While findings that female happiness has declined more rapidly than males’ are not uncontested, raw data from the Household, Income and Labour Dynamics in Australia (HILDA) survey appear to show a statistically significant decline in life satisfaction for females between 2001 and 2011; therefore making females now as 'miserable’ as men have always been. This thesis investigates if declining social connectedness presents a possible explanation for the observed declines in self-reported female life satisfaction in Australia over the first decade of the 21st century. Results indicate a positive association between all four measures of social connectedness and life satisfaction. Trends in social connectedness, however, are less clear; two of the four measures (participation in a hobby or community-based club or association and frequency of social interaction) have declined, whereas two measures (sense of belonging and tangible support) have improved over the period. There is some indication that the quality and quantity of social interactions differs between males and females and may play a role in declining life satisfaction. Therefore, fostering social connectedness would appear to be one channel through which social welfare might be promoted.
Keywords: Health -- Wellbeing; Social Capital; Gender -- Female; Satisfaction -- Life; Health and wellbeing; Gender; Health; Satisfaction; Gender; Social Capital; Wellbeing; Female; Life; Gender; Health and wellbeing